Fine tuning of trehalose biosynthesis and hydrolysis as novel tools for the generation of abiotic stress tolerant plants - Delorge, Ines; Janiak, Michal; Carpentier, Sebastien; Van Dijck, Patrick (Frontiers in Plant Science, 2014)
The impact of abiotic stress on plant growth and development has been and still is a major research topic. An important pathway that has been linked to abiotic stress tolerance is the trehalose biosynthetic pathway. Recent findings showed that trehalose metabolism is also important for normal plant growth and development. The intermediate compound – Trehalose-6-Phosphate (T6P) – is now confirmed to act as a sensor for available sucrose, hereby directly influencing the type of response to the changing environmental conditions. This is possible because T6P and/or trehalose or their biosynthetic enzymes are part of complex interaction networks with other crucial hormone and sugar-induced signalling pathways, which may function at different developmental stages. Because of its effect on plant growth and development, modification of trehalose biosynthesis, either at the level of T6P synthesis, T6P hydrolysis or trehalose hydrolysis, has been utilized to try to improve crop yield and biomass. It was shown that alteration of the amounts of either T6P and/or trehalose did result in increased stress tolerance, but also resulted in many unexpected phenotypic alterations. A main challenge is to characterize the part of the signalling pathway resulting in improved stress tolerance, without affecting the pathways resulting in the unwanted phenotypes. One such specific pathway where modification of trehalose metabolism improved stress tolerance, without any side effects, was recently obtained by overexpression of trehalase, which results in a more sensitive reaction of the stomatal guard cells and closing of the stomata under drought stress conditions. We have used the data that have been obtained from different studies to generate the optimal plant that can be constructed based on modifications of trehalose metabolism.